Determination of shear force capacity of H-type box furniture joints connected with different demountable type of connection elements. Issue 8 (17th April 2020) - Yıldırım, Mehmet Nuri; Karaman, Abdurrahman; Uslu, Esra
Abstract: In this study, the performances of type of demountable connectors used as connecting elements in the frame construction furniture are compared with the forces against shear force. The test samples were prepared from melamine-coated particle board (YL-Lam) and medium density fiberboard (MDF-Lam). Four types of demountable type of connection elements are used: metal L connection, plastic T connection, metal T connection and moon connection. The experimental samples were subjected to static stress tests under the critical loads that could be affected during the use. As a result of the experiments, the highest shear force was obtained from the test specimens prepared by using MDF-Lam and metal T connectors. The lowest was determined by using YL-Lam and plastic T connector. According to the results of the experiment, in the H type construction prepared with YL-Lam, when the shear force bearing capacity of the connection element is ordered from highest to lowest, respectively; Metal T, Moon, Metal L and Plastic T connectors were determined while in the construction prepared with MDF-Lam it is ordered as Metal T, Metal L, Plastic T and Moon connectors. In this study, the load-bearing capacity of the test samples and the load-deflection graph formed under this loading are given.